Sexually transmitted diseases control in developing countries. - Adler, M W (1996)
Sexually transmitted diseases (STDs) are a major public health problem now compounded by the advent of AIDS and HIV infection. The size of the problem represented by STDs and HIV is unknown however it is estimated that there are 333 million new cases of STD per annum and currently 15-20 million people infected worldwide with HIV. Control programmes for STDs must prevent the acquisition of STDs, their complications and sequelae and interrupt and reduce transmission. They can also reduce the incidence of HIV infection. Such programmes must place emphasis on health education, condom usage, altering health seeking behaviour and providing case management. The syndromic approach currently offers the most realistic, and cost effective, way in which to treat patients.